Demokratischer Übergang und Sozialdemokratie in Spanien: Kritische Überlegungen zur Konstruktion von Idealtypen - Hershberg, Eric (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
The author argues that the Spanish transition from authoritarianism to liberal democracy as well as the so called social democratic approach to modemization have been stylized into ideal types in the Weberian sense of the term. The Spanish model has gamered widespread attention. lts influence transcends the academic sphere, as Spain has provided political elites across the world with a model of regime change, especially in Latin America and Eastem Europe, where observers are intrigued both by the facility with which transition took place and by Spain’s reencounter with the prosperous zones of Western Europe. These idealizations are confronted with the real costs of Spains transition and the democratic deficits of the Spanish Socialists management of crisis.